The Effect of Using Educational Games and Cooperative Learning on Learning Some Floor Exercises in Artistic Gymnastics for 5th Grade Pupils - Karim, Fatima; Salim, Suzan (Journal of Physical Education, 2020)
The problem of the research lies in the lack of attention to artistic gymnastics in primary schools and not using it to teach female pupils some skills as well as the lack of using educational games and cooperative learning in teaching those pupils. The research aimed at identifying the effect of educational games and cooperative learning on learning some floor exercises in artistic gymnastics for 5th-grade pupils. In addition to that, the research aimed at designing educational games and cooperative learning to study their effect on learning some floor exercises skills in artistic gymnastics for 5th grade pupils. The subject of the research was (10) female pupils for each group from Noor Al Shames Primary School. The main experiment was applied within (8) weeks with 3 educational sessions per week making a total of 24 educational sessions for each group. The results showed a significant effect in learning floor exercises and the researchers concluded that using educational games and cooperative learning plays a great role in learning floor exercises in artistic gymnastics for both groups. the researchers recommended the necessity of using both strategies in teaching due to their great effect in teaching basic skills in gymnastics.